IDENTIDADES AFRO-BRASILEIRAS: CONTAS E ROSÁRIOS - Souza, Florentina (Caderno CRH, 2006)
Mapeando textos que tratam da questão etnicidade, este trabalho toma a imagem das contas do rosário como operador de leitura para abordar as produções discursivas que, através da história, elaboram as identidades étnicas na diáspora negra no Brasil. PALAVRAS-CHAVE: Etnicidade, identidades, afro-descendentes, diáspora, poesia negra. AFRO-BRAZILIAN IDENTITIES: BEADS AND ROSARIES Through the mapping of texts which deal with the issue of ethnicity, this paper takes the image of the rosary beads as a reading operator to address discourse productions that, in the course of history, draw up the ethnic identities in the Black diaspora in Brazil. KEYWORDS: Ethnicity, identities, Afro-descendents, diaspora, Black poetry. Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br